2021
DOI: 10.1186/s13643-020-01561-w
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of sepsis using artificial intelligence: a scoping review protocol

Abstract: Background Sepsis is a life-threatening organ dysfunction caused by a dysregulated host response to infection. To decrease the high case fatality rates and morbidity for sepsis and septic shock, there is a need to increase the accuracy of early detection of suspected sepsis in prehospital and emergency department settings. This may be achieved by developing risk prediction decision support systems based on artificial intelligence. Methods The overa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…Machine learning models are able to capture high-capacity relationships and they are amenable to more operational tasks rather than direct research questions; thus, more research gaps could be solved through the one-stop analysis [ 38 ]. Various medical data analyses used a machine learning approach to make decisions [ 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. Biostatisticians are in a need of an updated methodology that uses a machine learning approach to conduct analysis on a variety of medical data [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…Machine learning models are able to capture high-capacity relationships and they are amenable to more operational tasks rather than direct research questions; thus, more research gaps could be solved through the one-stop analysis [ 38 ]. Various medical data analyses used a machine learning approach to make decisions [ 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. Biostatisticians are in a need of an updated methodology that uses a machine learning approach to conduct analysis on a variety of medical data [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…Positive outcomes are highly related to effective management in EDs and ward settings since successful treatment is time-dependent. [36] Unfortunately, transferring patients from the ED or ward to an ICU is often ineffective. [36] A recent meta-analysis of 28 papers looking at ML for predicting sepsis found that diagnostic test accuracy when assessed using AUROC was 0.68–0.99 in the ICU, 0.96–0.98 in the hospital, and 0.87–0.97 in the ED.…”
Section: Early Detection: Diagnosing Sepsis On the Ward In The Ed And...mentioning
confidence: 99%
“…In its prognosis, successful treatment is time-dependent, where recommendations to initiate antibiotic therapy within the first hours of disease presentation and timely monitoring positively interfere with outcomes. Although highly desirable, early diagnosis is challenging given the nonspecific nature of signs and symptoms, as well as their similarity to other pathologies (4)(5) . In this scenario of care to the patient with sepsis, the performance of the multidisciplinary team is essential, especially the nursing team, because it is at the bedside, providing assistance, monitoring and evaluating the developments of hospitalization (6) .…”
Section: Introductionmentioning
confidence: 99%